1995
DOI: 10.1097/00000539-199512000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Four Bedside Methods of Hemoglobin Assessment During Cardiac Surgery

Abstract: The purpose of this study was to compare the accuracy of conductivity, adjusted conductivity, photometric, and centrifugation methods of measuring or estimating hemoglobin (Hb) with Coulter measured HB as the reference. These bedside methods were studied in 25 cardiac surgery patients during euvolemia and hemodilution and after salvaged autologous red blood cell transfusion. In vivo patient blood samples were obtained before induction, at the start of cardiopulmonary bypass (CPB), after CPB, and after blood tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Spielmann et al found two different clinical blood gas analyzers (CBGA-1 and CBGA-2) to have a higher mean Hb concentration (5.8–8.0 g/L) and one analyzer (CBGA-3) to have a lower mean Hb concentration (0.5 g/L) compared with the reference. 138 When applying the mean concentration difference threshold of ±7% for the studies comparing the other portable photometric invasive POC analyzers or clinical laboratory blood gas analyzers with the reference, 11 studies including 17 comparisons 18,31,43,102,106,110,113,120,121,138 met the allowable degree of variation with one study exceeding the ±7% bias 42 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Spielmann et al found two different clinical blood gas analyzers (CBGA-1 and CBGA-2) to have a higher mean Hb concentration (5.8–8.0 g/L) and one analyzer (CBGA-3) to have a lower mean Hb concentration (0.5 g/L) compared with the reference. 138 When applying the mean concentration difference threshold of ±7% for the studies comparing the other portable photometric invasive POC analyzers or clinical laboratory blood gas analyzers with the reference, 11 studies including 17 comparisons 18,31,43,102,106,110,113,120,121,138 met the allowable degree of variation with one study exceeding the ±7% bias 42 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…After a vaginal delivery, a spun Hct value was determined for each patient using the average of three spun samples from a finger prick at 12 hours postpartum, a method shown to correlate well with laboratory Hct values. 14 For patients who underwent cesarean delivery, a complete blood count was performed at 12 hours postoperative. Calculated EBL (cEBL) was determined using a validated method in which maternal blood volume {0.75 × [(maternal height in inches × 50) + (maternal weight in pounds × 25)]} is multiplied by percent of blood volume lost [(predelivery Hct − postdelivery Hct)/predelivery Hct].…”
Section: Methodsmentioning
confidence: 99%
“…The choice of methods has implications for the end-user, who must understand the limitations of each device. For instance, the use of different point-of-care devices for measuring hemoglobin was shown to have varying results [33]. Apart from the specific platform (i.e.…”
Section: 0 Blood Management Programmentioning
confidence: 99%